2018
DOI: 10.1016/j.jaerosci.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Subject-variability effects on micron particle deposition in human nasal cavities

Abstract: A B S T R A C TValidated computer simulations of the airflow and particle dynamics in human nasal cavities are important for local, segmental and total deposition predictions of both inhaled toxic and therapeutic particles. Considering three, quite different subject-specific nasal airway configurations, micron-particle transport and deposition for low-to-medium flow rates have been analyzed. Of special interest was the olfactory region from which deposited drugs could readily migrate to the central nervous sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 78 publications
1
30
0
Order By: Relevance
“…(55) This is of particular importance as the olfactory route is one of the proposed mechanisms for nanoparticle translocation to the brain. (36) Despite that in the studies modeling nasal deposition only a few micron-sized particles deposit on the olfactory region, (56) the NP-collectors could play an important role in nanoparticles translocation to the brain as their surface is enriched with multiple INPs. In addition, the translocation is expected to only occur for individual or a few nanoparticles agglomerates; which in both cases implies a de-agglomeration process.…”
Section: Discussionmentioning
confidence: 99%
“…(55) This is of particular importance as the olfactory route is one of the proposed mechanisms for nanoparticle translocation to the brain. (36) Despite that in the studies modeling nasal deposition only a few micron-sized particles deposit on the olfactory region, (56) the NP-collectors could play an important role in nanoparticles translocation to the brain as their surface is enriched with multiple INPs. In addition, the translocation is expected to only occur for individual or a few nanoparticles agglomerates; which in both cases implies a de-agglomeration process.…”
Section: Discussionmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) simulations have been widely used to provide information about human airways, including airway resistance, energy expended during breathing (work of breathing), distribution of airflow, transfer of heat and moisture, and particle deposition . Other methods are unable to provide this level of information due to the impracticalities of using flow instrumentation in the airway.…”
Section: Introductionmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) simulations have been widely used to provide information about human airways, including airway resistance, energy expended during breathing (work of breathing), distribution of airflow, transfer of heat and moisture, and particle deposition. [1][2][3][4][5][6] Other methods are unable to provide this level of information due to the impracticalities of using flow instrumentation in the airway. The metrics provided by CFD are becoming increasingly useful clinically and have been used to assess the effort of breathing in goiters [7][8][9] in transplanted tracheas, 10 stenotic pediatric tracheas, 11 and nasal obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of studies [45,58,106] has been conducted to predict the aerosol particle deposition in the extrathoracic region of the human lung using idealized anatomical models of circular or elliptic or constant diameter [107,108]. Recently, realistic CT/MRI based [109][110][111] anatomical models have been used to predict the local deposition in the extrathoracic airways. Xi and Longest [62] conducted a comparative study for local deposition in the mouth throat to larynx for different anatomical (realistic, circular, elliptic, fixed diameter) models and concluded that the CT-based realistic model provided the most accurate prediction of the experimental measurements.…”
Section: Extrathoracic Regionmentioning
confidence: 99%